2016
DOI: 10.1111/exd.12905
|View full text |Cite
|
Sign up to set email alerts
|

Locally advanced basal cell carcinoma has a distinct methylation and transcriptomic profile

Abstract: noninflamed follicular comedones and with postinflammatory pigmentation. C. Postinflammatory hyperpigmentation HS scars. D. Comparison of a normal and mutant partial chromatograph of DNA from family UR-252. The insertion of 2-nt (CC) at nucleotide position 687 of human NCSTN is shown. E. The truncated protein is predicted to terminate at codon 261 after the addition of 31 novel amino acids within exon 6 of NCSTN. Figure S2. A. Family UR-253 with acne conglobata (AC) was previously reported by Chandramohan (S17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…A small number of studies have been conducted on tumour suppressor methylation in BCC. Brinkhuizen et al 12 reported that locally advanced basal cell carcinoma has a distinct methylation and transcriptomic profile. Mutations of the PTCH hallmark gene are detected in 50%–60% of BCCs, and PTCH promoter methylation is at a lower level (31%) 13 .…”
Section: Introductionmentioning
confidence: 99%
“…A small number of studies have been conducted on tumour suppressor methylation in BCC. Brinkhuizen et al 12 reported that locally advanced basal cell carcinoma has a distinct methylation and transcriptomic profile. Mutations of the PTCH hallmark gene are detected in 50%–60% of BCCs, and PTCH promoter methylation is at a lower level (31%) 13 .…”
Section: Introductionmentioning
confidence: 99%